Sosialisasi Tentang Industri Kreatif di Kelurahan Pabundukang, Kabupaten Pangkep - Nurul Mukhlishah; Helda Ibrahim; Andi Asikin Muchtar (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
This service aims to provide socialization related to community knowledge and skills in managing economic benefits and business opportunities. Community service activities use three approaches, namely the lecture approach, experience sharing, and discussion. The research location was conducted in Pabundukang Village, Pangkajene District, Pangkep Regency, with a total sample of 20 people as respondents. The results of the dedication show that the results are significant. Due to the results of the comparison before and after the socialization of knowledge, the results showed that the percentage increased was quite high. Therefore, it can be suggested that community service activities in the Pabundukang sub-district, Pangkajene District, Pangkep Regency can be carried out regularly so that the community always has new or up-to-date knowledge so that they can compete in the creative industry.